Development Practices in Senior Nursing and Midwifery Leadership: Pathways to Improvement in South Pacific Health Policy. (August 2022) - Rumsey, Michele; Iro, Elizabeth; Brown, Di; Larui, Michael; Sam, Harriet; Brooks, Fiona
The Pacific Islands countries consist of thousands of isolated islands with a combined population of over 10 million people. It is a heterogeneous and diverse region culturally, linguistically economically and politically. Health challenges are considerable and healthcare systems are often overstretched. Framed in the context of the World Health Organisation's strategic directions and policy priorities, this paper describes an account of collaboration across these countries to develop leadership skills in the nursing and midwifery professions. It outlines lessons for nursing leadership, healthcare policy development and the valuable role of Government Chief Nursing and Midwifery Officers. The South Pacific Chief Nursing and Midwifery Officers Alliance (SPCNMOA) is a cooperative partnership, which was formed to improve the quality of healthcare in the region. It acts as an enabler to promote leadership skills and provide a safe space for learning, developing policy and the sharing of good practice. Through mentorship programs, international meetings and strong relationship-building, the SPCNMOA has strengthened partnerships within the region and improved community health services in even the most remote areas. By strengthening leadership and collaboration, these health professionals are now recognised by key policy makers as knowledgeable experts who have a legitimate role in guiding policy development, changing practice and delivering health policy improvements at local, country and international levels.